2009
DOI: 10.1351/pac-rep-08-04-02
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of mercury (IUPAC Technical Report)

Abstract: Republication or reproduction of this report or its storage and/or dissemination by electronic means is permitted without the Immunological effects of mercury (IUPAC Technical Report)Abstract: Various chemical species of mercury differ considerably with regard to their route of absorption and their distribution in the body, yet many of them and their metabolites exhibit high-affinity binding to sulfanyl groups of proteins. Among all metals, mercury appears to have the most diverse effects on the immune system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 115 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…Mercury exposure is associated with a wide range of adverse human health effects, including neurological, cardiac, motor, reproductive, genetic, renal, and immunological conditions [25,26,27,28,29,30,31]. Exposure to elemental mercury vapors can result in tremors, a decrease in memory performance, and a decrease in autonomic nervous system functioning [32].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury exposure is associated with a wide range of adverse human health effects, including neurological, cardiac, motor, reproductive, genetic, renal, and immunological conditions [25,26,27,28,29,30,31]. Exposure to elemental mercury vapors can result in tremors, a decrease in memory performance, and a decrease in autonomic nervous system functioning [32].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, zinccontaining amalgams are more cytotoxic due to easy release of Zn ions. The toxic effects of mercury are believed to be due to the high reactivity of mercury species toward thiolgroups and other functional groups, notably in proteins 27 . It has been shown that both organic and inorganic mercury induce apoptosis of different cells including human lymphocytes 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The different forms of mercury are highly toxic at relatively low dosages and can produce varying health effects [ 3 , 20 ]. Toxicity of mercury substances arises mainly from destructive bonding to thiol (-SH), contained in sulfhydryl and selenohydryl groups [ 21 ]. In addition, mercury bonds to phosphoryl, carboxyl, amide, and amine groups.…”
Section: Mercury Speciation and Toxicitymentioning
confidence: 99%
“…Elemental, or metallic mercury, is unique in being the only metal element that is liquid at room temperature and highly volatile at relatively low temperatures. The main sources of metallic mercury for humans are dental amalgams and workplace exposures [ 1 , 2 , 21 , 22 ].…”
Section: Mercury Speciation and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation